Role of Spexin in White Adipose Tissue Thermogenesis under Basal and Cold-Stimulated Conditions - Gambaro, Sabrina Eliana (2024)
Spexin (SPX) is a novel adipokine that plays an emerging role in metabolic diseases due to its involvement in carbohydrate homeostasis, weight loss, appetite control, and gastrointestinal movement, among others. In obese patients, SPX plasma levels are reduced. Little is known about the relationship between SPX and white adipose tissue (WAT) thermogenesis. Therefore, the aim of the present study was to evaluate the role of SPX in this process. C57BL/6J male mice were treated or not with SPX for ten days. On day 3, mice were randomly divided into two groups: one kept at room temperature and the other kept at cold temperature (4 ◦C). Caloric intake and body weight were recorded daily. At the end of the protocol, plasma, abdominal (epididymal), subcutaneous (inguinal), and brown AT (EAT, IAT, and BAT, respectively) depots were collected for measurements. We found that SPX treatment reduced Uncoupling protein 1 levels in WAT under both basal and cold conditions. SPX also reduced cox8b and pgc1α mRNA levels and mitochondrial DNA, principally in IAT. SPX did not modulate the number of beige precursors. SPX decreased spx levels in IAT depots and galr2 in WAT depots. No differences were observed in the BAT depots. In conclusion, we showed, for the first time, that SPX treatment in vivo reduced the thermogenic process in subcutaneous and abdominal AT, being more evident under cold stimulation.